Position Statement on the Effects of Cigarette Smoke on Allergic Diseases - Sandejas, Arlene Grace; Valerio, Maria Rowena; Rodolfo, Jacqueline; Ponio-Baloyo, Gina Marie (Philippine Journal of Allergy, Asthma and Immunology, 2023)
Environmental tobacco smoke exposure is one of the major causes of air pollution that has been suspected to play a role in the rise of allergic diseases worldwide. Studies have shown that exposure to environmental tobacco smoke during pregnancy and during childhood increases the risk of developing not only allergic airway diseases but also allergic skin diseases. Smokefree legislation has been shown to help in decreasing the burden of allergic diseases in the country. Thus, we fully support the implementation of smokefree legislation in the hope that it will continue to decrease the number of smokers in the country. We strive to educate our patients against the ill effects of environmental tobacco smoke and continue to urge current smokers to quit smoking, not only for themselves but for their entire family.